PREVALÊNCIA DO VÍRUS LINFOTRÓPICO DE CÉLULAS T HUMANAS TIPOS 1 e 2 EM GESTANTES, SÃO LUÍS- MA. - Souza, Verônica Guimarães de (2009)
INDTRODUCTION: HTLV are retroviruses with tropism for lymphocytes T, type 1 (HTLV-1) is endemic in the Caribbean region, Japan, South America, and parts of Africa; type 2 in some American native groups, rare in Africa, and the Europe associated with use of injectable drugs. In Brazil one esteem 2,5 million infected people in all the states where it was searched, with some prevalence. OBJECTIVE: This study had the objective identify the prevalence of HTLV-1 and 2 in the selection of pregnant taken care of in the prenatal one of three public services. METHODOLOGY Transversal study, carried through between 11/02 and 03/12/2008, with 2044 pregnant in three public services of prenatal, São Luis/MA. Patients had been guided on the study and enclosed after signature of the TCLE and filling of the questionnaire. They had participated pregnant between 18 and 45 years, without history of psychiatric illnesses, high blood pressure, kidney pathology, diabetes and others that would characterize specialized necessity of prenatal. The sample was calculated in 2041, to be able of the test of 95%, absolute error of 5%, was used program Stata 9,0, carried through test qui squared and accepted p< 0,05 (95%) as limit for significance. In the selection collection of digital blood in processed paper was used filter and in the laboratory of NUPAD - MG, to be submitted to ELISA test. The pregnant that had presented resulted modified had been contacted for new collection of peripheral vein blood for confirmatory tests western blot and PCR.RESULTS Of the 2044 evaluated pregnant, 7 pregnant had presented resulted modified, 01 indeterminate and 06 positives, showing prevalence of 0.34%. CONCLUSION This research MOSTROU that prevalence is higher then on blood donators and is necessary ampler studies and that they contemplate other extracts of the population to identify the reality of the presence of the virus in the State of the Maranhão.